A novel analytical model for optimal sizing of standalone photovoltaic systems energy. - Jakhrani, A.Q.; Othman, A.K.; Rigit, A.R.H.; Samo, S.R.; Kamboh, S.A (Elsevier Ltd, 2012)
This paper presents a novel analytical model for the determination of optimal sizing of novel of standalone photovoltaic (PV) systems with least cost and predetermined reliability to satisfy load. Algebraic equations for optimal PV array area (Aopt), optimal useful battery storage capacity (Cu,opt) and the constant of integration (kopt) has been formulated. The proposed model provides the system output directly without going through the calculation of PV array capacity (Ca) and battery storage capacity (Cb). It is different from previous models, which only optimize the system parameters Ca and Cb without involving load. The isoreliability curves of proposed model are compared with other analytical and numerical methods with the pair of Ca and Cb in different environmental conditions without load involvement. The formulated model is also applied for the optimal sizing of a standalone PV system for domestic purpose at Kuching, Sarawak, Malaysia. The required optimal PV array area (Aopt) and useful battery storage capacity (Cu,opt) is determined with various load demands and loss of load probability (LLP). Proposed analytical model is more constructive due to incorporation of many useful variables namely desired LLP value, latitude and clearness index of location, load demand and unit cost of PV array and battery capacity. It is also rational in terms of power reliability and cost, and simple to implement for the size optimization of standalone PV systems as compared to existing models.